Müllerianosis of the urinary bladder in pre- and postmenopausal women: a literature review - Diamantidis, Dimitrios; Tsakaldimis, Georgios; Lailisidis, Stavros; Deligeorgiou, Evangelia; Panagiotopoulos, Nikolaos; Kritsotaki, Nektraria; Kafalis, Charalampos; Chousein, Chousein; Giannakopoulos, Stilianos; Kalaitzis, Christos (Menopause Review/Przegląd Menopauzalny, 2024)
Müllerianosis of the urinary bladder is a rare pathological condition involving ectopic Müllerian-derived tissues within the bladder. Despite its benign nature, due to its ability to mimic malignant conditions such as bladder carcinoma, diagnosis might be challenging. In this review, data from 36 cases across 32 studies were analyzed, focusing on patient demographics, symptomatology, diagnostic imaging, and histopathological features. The average patient age was 42.4 years. Common symptoms included dysuria, hematuria, and pelvic pain. Diagnostic challenges arise from the nonspecific nature of symptoms and imaging findings, making histopathological confirmation necessary. Surgical treatment is mainly involved, with transurethral resection being the most common approach. In some cases, hormonal therapy is also explored. While the prognosis is generally favorable, recurrence is possible, emphasizing the need for long-term follow-up. The review underscores the importance of early diagnosis and individualized management strategies to improve patient outcomes.